Cutaneous nociception: Role of keratinocytes. Issue 12 (24th June 2019) - Talagas, Matthieu; Lebonvallet, Nicolas; Berthod, François; Misery, Laurent
Abstract: Recent years have brought an enhanced understanding of keratinocyte contribution to cutaneous nociception. While intra‐epidermal nerve endings were classically considered as the exclusive transducers of cutaneous noxious stimuli, it has now been demonstrated that epidermal keratinocytes can initiate nociceptive responses, like Merkel cells do for the innocuous mechanotransduction. In the light of recent in vivo findings, this article outlines this paradigm shift that points to a not yet considered population of sensory epidermal cells.